Investigation of Heavy Metal Contamination in Fishes from Passur River near the Sundarbans Mangroves of Bangladesh (Journal of Environmental Science and Natural Resources, 2017)
The study was conducted to investigate the heavy metal contamination in fishes and shrimps from the Passur River near the world famous Sundarban mangroves located in the southwestern part of Bangladesh, during the period from January to June 2013. The fish (Liza parse) and shrimp (Penaeus monodon) samples were collected from two stations as St-1 (Katakhali-1 km upper from port area- upstream) and St-2 (Amtola-1 km lower from port area- downstream) monthly for three months in January (winter), March (pre monsoon) and May (Monsoon). Before analysis, a bit of muscle, the whole liver and two gill arches from each fish and shrimp were removed. Samples of tissues from each fish and shrimp were removed, weighed and dried. A microwave digestion system was used to prepare the samples for analysis. After digestion residue diluted with 25 ml 2.5% HNO3. The water used was deionized and distilled. The metal analyses of samples (Cd, Cr, Cu, Pb and Zn) were carried out by using UNICAM-929 atomic absorption spectrophotometer (AAS) in SGS Bangladesh Limited, Dhaka-1205, Bangladesh. Among the heavy metals studied Cd, Cr, Cu, Pb and Zn were detected in fish and shrimp species were within acceptable limits by FAO standards. The results of this study indicated that a general absence of serious pollution in the Passur River is due to heavy metals; whereas the concentrations of elements found could mainly be attributed to geological sources. In this regard, to maintain the water and sediment qualities as well as the sound and safe aquatic life of the river need proper monitoring and management by the relevant authorities of the Government of Bangladesh.J. Environ. Sci. & Natural Resources, 10(1): 21-24 2017